Global Estimation of Myelination in the Developing Brain on the Basis of Magnetization Transfer Imaging: A Preliminary Study - van Buchem, Mark A.; Steens, Stefan C.A.; Vrooman, Henri A.; Zwinderman, Aeilko H.; McGowan, Joseph C.; Rassek, Margarethe; Engelbrecht, Volkher (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: In the developing brain, myelination occurs in an orderly and predetermined sequence. The aim of this study was to determine whether such changes can be tracked using volumetric magnetization transfer imaging.METHODS: Three-dimensional magnetization transfer imaging was performed in 50 children (age range, 0.6–190 months) with no evidence of developmental delay or structural abnormalities. Volumetric magnetization transfer ratio (MTR) parameters generated of the whole brain were mean MTR and height and location of the MTR histogram peak. Relationships between volumetric MTR parameters and age were assessed using nonlinear regression analysis.RESULTS: With age, all volumetric MTR parameters changed exponentially in a way that was best expressed by the function y = a + b.exp(−x/c) (P < .0001). The peak height of the MTR histogram was the parameter that changed most predictably and that continued to change for the longest period of time.CONCLUSION: With this preliminary study, we show that by using volumetric MTR analysis, it is possible to monitor changes in the developing brain, presumably the myelination progress. This method has a potential role for detecting myelination disorders in the pediatric population, for studying the natural history of these diseases, and for monitoring the effects of treatment.